Mambokadzi - Chiwa, Akudzwe Elsie (Michaelis School of Fine Art, 2022)
Mambokadzi is built around the stories of my matrilineal histories and centred on the intimate space in which my grandmother, mother and I exist. It also seeks to recognize the collective space of Black womxn through an exploration of the royal ancestral spirit Nehanda who instigated the first Chimurenga (resistance-struggle) of 1896-97. This space is one tainted by colonial and patriarchal trauma, yet concurrently subverts colonial ideas of gender, particularly the feminine. Mambokadzi is intended to embody a decolonial idea of gender and femininity. In this collective space, womxn have consciously and unconsciously cultivated power within the confines of patriarchy, masculinity and coloniality. Through sculpture, I interrogate learned perceptions about gender and reflect on experiences of womxn in my family as a way to discuss womxnhood in Southern Africa and the diaspora broadly